Implementasi Etika Bisnis Islam pada Rumah Makan Ayam Squer Kota Mataram - Nur’Aini Nur’Aini; Suwandi Suwandi; Baiq Reinelda Tri Yunarni (Journal of Sharia Economy and Islamic Tourism, 2024)
Abstract: This research aims to analyze the application of sharia business ethics at Squer Chicken Restaurant in Mataram City. Sharia business ethics are guidelines that direct business practices to be in accordance with Islamic principles, which include unity, balance, free will, responsibility and virtue. The method used in this research is a qualitative study with a descriptive approach. The research results show that Squer Chicken Restaurant applies the principle of oneness by guaranteeing halal and quality products, as well as prioritizing the principle of balance in a price strategy that is affordable for various groups. In addition, the principle of free will is implemented through a strong commitment in the employment contract, while the principle of responsibility is manifested in consistent pricing on all menus. Lastly, the principle of benevolence is implemented through friendly and fair service to customers. The overall implementation of sharia business ethics not only supports business sustainability, but also increases customer satisfaction and loyalty.Abstrak: Penelitian ini bertujuan untuk menganalisis penerapan etika bisnis syariah pada Rumah Makan Ayam Squer di Kota Mataram. Etika bisnis syariah merupakan pedoman yang mengarahkan praktik bisnis agar sesuai dengan prinsip-prinsip Islam, yang mencakup keesaan, keseimbangan, kehendak bebas, tanggung jawab, dan kebajikan. Metode yang digunakan dalam penelitian ini adalah studi kualitatif dengan pendekatan deskriptif. Hasil penelitian menunjukkan bahwa Rumah Makan Ayam Squer menerapkan prinsip keesaan dengan menjamin produk yang halal dan berkualitas, serta mengedepankan prinsip keseimbangan dalam strategi harga yang terjangkau untuk berbagai kalangan. Selain itu, prinsip kehendak bebas diterapkan melalui komitmen yang kuat dalam kontrak kerja, sementara prinsip tanggung jawab diwujudkan dalam penetapan harga yang konsisten pada semua menu. Terakhir, prinsip kebajikan diimplementasikan melalui pelayanan yang ramah dan adil kepada pelanggan. Keseluruhan penerapan etika bisnis syariah ini tidak hanya mendukung keberlanjutan usaha, tetapi juga meningkatkan kepuasan dan loyalitas pelanggan.